Experimental investigation of femtosecond laser micro/nano processing of quartz material. Issue 197 (24th March 2019) - Wang, You; She, Ting; Liu, Defeng; Dai, Yutang; Lin, Hongfeng
Abstract: Quartz material is widely used in the automotive industry, aerospace, optical and electronic fields and so on. But quartz is a hard and brittle material, which makes it very difficult to process. Femtosecond laser is applied to micro/nano processing of quartz material due to its excellent performance. This paper uses different energy density femtosecond lasers to process quartz materials and analyzes the surface morphology. The experimental results show that the etching threshold of quartz material is 4.63 J/cm 2 . The etching depth of the single pulse and the femtosecond laser beam waist radius are 0.005 μm and 8.7 μm, respectively. Besides, there are some granular characteristics on the side wall of etching groove that affect surface quality. The larger the laser power, the more deposits there are.